Paul and his social relations - Porter, Stanley E., 1956-; Land, Christopher D. (Pauline Studies, 2013)
Pauline scholars have always been interested in Paul's relationships. In fact, some of the most influential developments in modern Pauline scholarship have been attempts to situate Paul socially. This volume addresses many of the questions surrounding Paul and his social relations, including how to define and analyze such relations, their relationship to Paul's historical and social context, how Paul related to numerous friends and foes, and the implications for understanding Paul's letters as well as his theology. As a result, a variety of methods are brought to an examination of Paul. These include explorations in social-scientific methodology, close readings of Paul's letters, and linguistically informed approaches to social relations. The conclusions well illustrate the importance of Paul's social relations and his own social connectedness.